Organophosphate esters in house dust: A comparative study between Canada, Turkey and Egypt - Shoeib, Tamer; Webster, Glenys M.; Hassan, Yasmeen; Tepe, Sedef; Yalcin, Melis; Kurt Karakuş, Perihan Binnur (Elsevier Science Bv, 2019)
Organophosphate esters (OPEs) are commonly used as flame retardants (FRs) and plasticizers. The usage of OPEs has increased recently due to the ban of several brominated flame retardants, but information on levels in the environment, including the indoor environment is still limited. We investigated the occurrence and distribution of 12 OPEs in urban house dust from Vancouver, Canada; Istanbul, Turkey; and Cairo, Egypt. The medianSOPE concentration was 41.4 mu g/g in the Vancouver samples while median levels in Istanbul and Cairo were significantly lower. The median composition profiles of OPEs in Vancouver and Cairo were dominated by tris (2-butoxyethyl) phosphate (TBOEP), accounting for 56 and 92% of total OPEs respectively while it showed a detection frequency of only 14% in Istanbul. Tris (2-chloropropyl) phosphate (TCPP) was the most abundant chlorinated OPE representing 20 and 36% of the total OPEs in Vancouver and Istanbul respectively, but was below the detection limit in the Cairo dust samples. Consistent with other studies, SOPE concentrations were similar to 1 to 2 orders of magnitude higher than PBDEs and currently used flame retardants in the same dust samples. The mean estimated daily intakes (EDI) of SOPE from dust were 115, 38 and 9 ng/kg/bw/day in Vancouver, Cairo and Istanbul respectively for toddlers where adults were similar to 10 times lower. The total toddler OPE intake ranged from 115 to 2900, 38 to 845 and from9 to 240 ng/kg bw/day across the three cities. TBOEP had the largest contribution to the EDI in both toddler and adults, where toddler TBOEP exposures via dust represented 4% to 80%, 2% to 44% and 0.1% to 6% of the Reference Doses (RfD) in the mean and high intake scenarios for toddlers in Vancouver, Cairo and Istanbul respectively. Crown Copyright (C) 2018 Published by Elsevier B.V. All rights reserved.
Keywords: Organophosphate esters; House dust; Exposure